Analisis Kesalahan Siswa dalam Menyelesaikan Soal Pemecahan Masalah Matematika Berdasarkan Newman’s Error Analysis di Kelas V Sekolah Dasar - Andayani, Nurlita; Kuntarto, Eko; Sastrawati, Eka (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The error analysis in this research is to determine the errors made by students in solving mathematics problem solving questions based on Newman's Error Analysis, which is a method for analyzing errors in problem solving problems. This research involved 19 students in class VB at SDN 14/I Sungai Baung. The interview subjects were 6 out of 19 VB class students, each consisting of 2 students from the upper, middle and lower groups. The selection of interview subjects was carried out using purposive sampling. Data collection techniques include tests and interviews. Validity of data using technical and time triangulation. The research results showed that of the five stages of error according to Newman's procedure, the subject made four errors in working on the data presentation material. The four errors are errors in understanding the problem, there are 42 errors with a percentage of 21.87%, transformation errors there are 27 errors with a percentage of 14.06%, process skills errors there are 58 errors with a percentage of 30.20%, errors in writing answers there are 65 errors with a percentage 33.85% and students did not make mistakes reading the problem. The reasons why students do this are not being used to writing down what they know/are asking about, not understanding/interpreting the problem in the question, not being skilled enough in carrying out the calculation process, not being careful/careless, and making mistakes at the previous stage.